A Review of the Mycotoxin Enniatin B - Prosperini, Alessandra; Berrada, Houda; Ruiz, María José; Caloni, Francesca; Coccini, Teresa; Spicer, Leon J.; Perego, Maria Chiara; Lafranconi, Alessandra (Frontiers in Public Health, 2017)
Mycotoxin Enniatin B (ENN B) is a secondary metabolism product by Fusarium fungi. It is a well known antibacterial, antihelmintic, antifungal, herbicidal and insecticidal compound. It has been found as a contaminant in several food commodities, particularly in cereal grains, co-occurring also with other mycotoxins. The primary mechanism of action of ENN B is mainly due to its ionophoric characteristics, but the exact mechanism is still unclear. In the last two decades, it has been a topic of great interest since its potent mammalian cytotoxic activity was demonstrated in several mammalian cell lines. Moreover, the co-exposure in vitro with other mycotoxins enhances its toxic potential through synergic effects, depending on the concentrations tested. Despite its clear cytotoxic effect, European Food Safety Authority (EFSA) stated that acute exposure to ENNs, such as ENN B, does not indicate concern for human health, but a concern might be the chronic exposure. However, given the lack of relevant toxicity data, no firm conclusion could be drawn and a risk assessment was not possible. In fact, very few studies have been carried out in vivo and, in these studies, no adverse effects were observed. So, research on toxicological effects induced by ENN B is still on-going. Recently, some studies are dealing with new advances regarding ENN B. This review summarizes the information on biochemical and biological activity of ENN B, focusing on toxicological aspects and on the latest advances in research on ENN B.